ҚАЗАҚСТАНДАҒЫ ЭЛЕКТРОНДЫ САУДАНЫҢ ДӘСТҮРЛІ САУДАДАН АЙЫРМАШЫЛЫҚТАРЫ МЕН ДАМУ МӘСЕЛЕЛЕРІ. (Journal of Economic Research & Business Administration, 2015)
В данной статье рассмотрены отличие электронной коммерции от традиционной торговли и проблемы вРК.***In given article are considered difference of electronic commerce from traditional trade and a problem in RK.